(untitled) (Culturas Científicas, 2022)
The search for an integrative pluralism in the philosophy of science has fruitful echoes in contemporary discussions of the philosophy of psychiatry, especially around the need for a pluralism that overcomes neurobiological reductionism and biopsychosocial eclecticism. The works of the philosopher Sandra Mitchell will constitute a starting point to visualize the need for a pluralistic paradigm, while they will allow to expose the thesis that a model is necessary that allows a real integration between the diverse relevant dimensions in psychiatry in order not to implicitly fall back into a reductionist pluralism. In this line, the perspectives that have emerged in psychiatry when it comes to achieving an integrative pluralism will be critically analyzed. Finally, the enactive model in cognitive science and its application in psychiatry will be reviewed as a possible alternative in search of an integration in psychiatry that allows an integrative pluralism at the ontological level, allowing a middle path between a neurocentric and an eclectic relativist psychiatry.